Diversity as the physical correlate to open space's experience in two historical towns - Harun, Nor Zalina; Mansor, Mazlina; Said, Ismail (Centre for Environment-Behaviour Studies, 2013)
This research studies diversity as a parameter in the built environment in two types of open spaces in colonial towns of Taiping and Georgetown. The richness of natural landscape elements, scales of spaces, distribution of activity patterns, and variety of visual stimulants in the open spaces were among the dimensions of diversity explored in this study. This paper is exploratory in nature, which applies a qualitative method. It involves descriptive and affective aspects of environmental experience of users of the two open spaces. The study suggests that diversity means socialization, which can be achieved through gradual and natural occurring assimilation.